2008
DOI: 10.1189/jlb.1107782
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Advance: Th-1 cytokines inhibit, and Th-2 cytokines promote fibrocyte differentiation

Abstract: CD14+ peripheral blood monocytes can differentiate into fibroblast-like cells called fibrocytes, which are associated with and are at least partially responsible for wound healing and fibrosis in multiple organ systems. Signals regulating fibrocyte differentiation are poorly understood. In this study, we find that when added to human PBMCs cultured in serum-free medium, the profibrotic cytokines IL-4 and IL-13 promote fibrocyte differentiation without inducing fibrocyte or fibrocyte precursor proliferation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
293
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(314 citation statements)
references
References 86 publications
19
293
0
2
Order By: Relevance
“…Although used successfully in multiple studies to relate TAM infiltration with clinically relevant outcomes, our results indicate that CD68 alone cannot accurately evaluate macrophage presence in human breast tissue given that multiple stromal cells express it and that a subset of these are CSF1R-and CD45-negative. We observed that the nonleukocytic CD68 + cells were predominantly located within tumor stroma and, thus, based on this localization and morphology, we speculate that CSF1R − CD68 + cells likely reflect tumor-associated fibroblasts or monocyte-derived fibrocytes in agreement with other reports (31,32,(49)(50)(51)(52). Our findings do not invalidate CD68 as a clinically relevant marker and, importantly, CSF1-response gene signatures have been identified in breast adenocarcinomas that are predictive of recurrence risk and metastasis (53,54).…”
Section: Discussionsupporting
confidence: 79%
“…Although used successfully in multiple studies to relate TAM infiltration with clinically relevant outcomes, our results indicate that CD68 alone cannot accurately evaluate macrophage presence in human breast tissue given that multiple stromal cells express it and that a subset of these are CSF1R-and CD45-negative. We observed that the nonleukocytic CD68 + cells were predominantly located within tumor stroma and, thus, based on this localization and morphology, we speculate that CSF1R − CD68 + cells likely reflect tumor-associated fibroblasts or monocyte-derived fibrocytes in agreement with other reports (31,32,(49)(50)(51)(52). Our findings do not invalidate CD68 as a clinically relevant marker and, importantly, CSF1-response gene signatures have been identified in breast adenocarcinomas that are predictive of recurrence risk and metastasis (53,54).…”
Section: Discussionsupporting
confidence: 79%
“…1A). As previously observed (31), the presence of TNF-α alone did not significantly affect fibrocyte differentiation (Fig. 1A).…”
Section: Significancesupporting
confidence: 66%
“…To test the hypothesis that activated fibroblasts might secrete soluble factors that promote fibrocyte differentiation, we added conditioned medium from human fibroblasts incubated with TNF-α (FCM+TNF-α) to human peripheral blood mononuclear cells (PBMC) in conditions where some of the monocytes in the PBMC would normally differentiate into fibrocytes. We used TNF-α as the stimulus, as other profibrotic cytokines such as IL-4, IL-13, and TGF-β act directly on monocytes to regulate fibrocyte differentiation (31). TNF-α is produced by monocytes, macrophages, and fibrocytes, serum TNF-α levels are increased in fibrosis patients, and TNF-α induces fibrosis in animal models (32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Fibrocytes were harvested and cultured as previously described (24,25). Briefly, peripheral blood mononuclear cells (PBMCs) were isolated from murine or human blood by using Lymphoprep™ (Progen Biotechnik).…”
Section: Culturing Murine or Human Fibrocytesmentioning
confidence: 99%